EFFICACY OF MINIMALLY INVASIVE TECHNOLOGY IN THE SURGICAL TREATMENT OF PANCREATIC CYSTS - Полвонниёзов Хумоюн Гайратжон угли; Отамирзаев Кудрат Абдужаббор угли; Ортикбоев Фарход Дилшод угли (Journals Park Publishing, 2023)
The relevance of the treatment of pancreatic cysts (pancreas) is determined by an increase in the incidence of pancreatitis, a significant number of complications and high lethality. In recent decades, there has been a steady increase in destructive forms of pancreatitis, respectively, the number of pancreatic cysts increases. Pancreatic cysts in 18-68% cause various complications (suppuration, perforation, bleeding, internal and external fistulas, malignancy), which determines a high mortality rate of 9.2-53%. The nature and scope of surgical intervention depend on the etiology, the presence or absence of a cyst connection with the ductal system, the presence of complications. The high prevalence of cystic lesions of the pancreas, the difficulties in choosing the optimal method of treatment require the creation of a rational, convenient for clinical practice diagnostic and therapeutic algorithm. Dissatisfaction with the results of treatment and a large number of complications prompt the search for a new, so-called gold standard for the treatment of patients and the definition of the real place of mini-invasive and open surgical methods.
Keywords: chronic pancreatitis, pancreas, pancreatic cyst, pseudocyst, mini-invasive surgery.